(3GdQhVI GdHgjI aj TQM GddeYI GdOeTbjIs - (3GdYGedj, GdLHYj, Rjf GdOjf Hf Ydj Hf CMeO, J (B966 (3g`s ((3YHO GdMejO Hf Ydjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj TQM UOhQfG HdeYI ef TQGFY GdESdGe(B... (3hHYO, agPg JYdjbI dWjaI (B... (3CVaJgG Edi GdeNJUQ GdTQja(B... (3GdehSheI HdeYI GdOeTbjI(B...s
(3BNQgG (B:s
(3hGdHGYK Ydjg Cj YHi GdePchQ GdeOdhd Ydjg HGdaYd(B... (3Cj WdH HYV GdWdGH hbO JbOe (B... (3hGdMeO ddg hMOg(B...s
(3JHUQI GdYfhGf (B:s
(3TQM GddeYI GdOeTbjIs
(3JHUQI GdeDda (B:s
(3GdTgjO GdKGfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B3(3, U(B64s
Keywords: (3abg GdePGgH GdCNQis